Why are some plant species missing from restorations? A diagnostic tool for temperate grassland ecosystems - De Vitis, Marcello; Havens, Kayri; Barak, Rebecca S.; Egerton-Warburton, Louise; Ernst, Adrienne R.; Evans, Matt; Fant, Jeremie B.; Foxx, Alicia J.; Hadley, Kyndall; Jabcon, Jim; O’Shaughnessey, Joan; Ramakrishna, Sai; et al. (Frontiers in Conservation Science, 2022)
The U.N. Decade on Ecosystem Restoration aims to accelerate actions to prevent, halt, and reverse the degradation of ecosystems, and re-establish ecosystem functioning and species diversity. The practice of ecological restoration has made great progress in recent decades, as has recognition of the importance of species diversity to maintaining the long-term stability and functioning of restored ecosystems. Restorations may also focus on specific species to fulfill needed functions, such as supporting dependent wildlife or mitigating extinction risk. Yet even in the most carefully planned and managed restoration, target species may fail to germinate, establish, or persist. To support the successful reintroduction of ecologically and culturally important plant species with an emphasis on temperate grasslands, we developed a tool to diagnose common causes of missing species, focusing on four major categories of filters, or factors: genetic, biotic, abiotic, and planning & land management. Through a review of the scientific literature, we propose a series of diagnostic tests to identify potential causes of failure to restore target species, and treatments that could improve future outcomes. This practical diagnostic tool is meant to strengthen collaboration between restoration practitioners and researchers on diagnosing and treating causes of missing species in order to effectively restore them.